(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was intended to provide basic data for discussion on the introduction of safety and health education system for business owners to prevent industrial accidents. To this end, a questionnaire survey was conducted on 548 occupational safety and health officials, of which 86.7% expected that the introduction of safety and health education for business owners would be very helpful in preventing accidents in the workplace. On the other hand, it was pointed out that the effectiveness of safety and health education for business owners needs to be raised as it deals with the areas considered to be important in the job and basic competencies of business owners. The study subjects also most highly agreed with the need for annual regular training for business owners at all workplaces.